IMPLEMENTATION OF PEDAGOGICAL ACTIVITY OF LABOUR PROTECTION SPECIALISTS IN WORK ENVIRONMENT - Brizga, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Human health and wellness are significantly affected by the observance of labour and civil protection rules both in the work environment and in social life. They are also affected by adequate training which is organised according to the age group and situation in order to reduce the formal attitude to the observance of all types of safety rules. Labour protection specialists themselves will be those who will respect and ensure the observance of the labour and civil protection rules. The aim of this study was to research the implementation of pedagogical activities of labour safety specialists in the work environment. The methodologies used in the research were semi-structured interviews, questionnaires and the analysis of the qualitative data and comments, submitted by labour protection specialists electronically, to clarify the implementation of pedagogical activities in the context of the UNESCO concept of sustainable development of education with the aim to reduce formal attitude towards the observance of labour and civil protection rules, using the model of ecological approach - Process–Person–Context–Time. The text analysis was carried out using the software programme Weft QDA. By improving labour protection specialists’ pedagogical competence, the staff’s (employers’, employees’) expertise also improves or partially improves.